Computational site-directed mutagenesis studies of the role of the hydrophobic triad on substrate binding in cholesterol oxidase - Harb, L.; Arooj, Mahreen; Vrielink, A.; Mancera, Ricardo (John Wiley & Sons, Inc., 2017)
© 2017 Wiley Periodicals, Inc. Cholesterol oxidase (ChOx) is a flavoenzyme that oxidizes and isomerizes cholesterol (CHL) to form cholest-4-en-3-one. Molecular docking and molecular dynamics simulations were conducted to predict the binding interactions of CHL in the active site. Several key interactions (E361-CHL, N485-FAD, and H447-CHL) were identified and which are likely to determine the correct positioning of CHL relative to flavin-adenine dinucleotide (FAD). Binding of CHL also induced changes in key residues of the active site leading to the closure of the oxygen channel. A group of residues, Y107, F444, and Y446, known as the hydrophobic triad, are believed to affect the binding of CHL in the active site. Computational site-directed mutagenesis of these residues revealed that their mutation affects the conformations of key residues in the active site, leading to non-optimal binding of CHL and to changes in the structure of the oxygen channel, all of which are likely to reduce the catalytic efficiency of ChOx. Proteins 2017; 85:1645–1655. © 2017 Wiley Periodicals, Inc.